Media conceptualizing illnesses – the case of the flu. Issue 1 (2nd January 2016) - Dobrić, Nikola; Weder, Franzisca
Abstract : The second half of last century and the beginning of the current one were marked by several major health crises caused by the widespread and often deadly flu epidemics. The paper investigates the academic medical discourse used by the media as the major initial source of information about the epidemic. The focus of the study is on the conceptual metaphors used in medical academic publications to portrait the flu as they seem to be the most semantically accessible linguistic units used by the media to transfer information from scientific discourse to the general public. Theoretical and practical implications of this information transfer as well as limitations of the study are discussed.